2019
DOI: 10.1002/hpm.2859
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on healthcare employee satisfaction between Japan and China

Abstract: Summary Objectives To explore essential characteristics of healthcare employee satisfaction by comparing Japan and China in terms of job satisfaction model, satisfaction level, and the crucial factors predicting overall job satisfaction. Methods A questionnaire was developed with 35 facet‐specific job‐related satisfaction and 10 general satisfaction items. The Japanese survey collected 474 responses (74% response rate). Two additional items were added in the Chinese survey and 429 responses were collected (69%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Compared to other studies investigating job satisfaction both in Sweden and in other countries [ 11 , 29 , 32 , 35 , 36 , 37 , 38 ], the present study, as well as the previous investigation in 2015 [ 19 ], showed that job satisfaction among the graduates was higher. Furthermore, a majority of graduates answered maybe or definitely yes to the question of whether they would start the same career if they were to choose again, thus indicating that most of the graduates were satisfied with their choice of career.…”
Section: Discussioncontrasting
confidence: 82%
“…Compared to other studies investigating job satisfaction both in Sweden and in other countries [ 11 , 29 , 32 , 35 , 36 , 37 , 38 ], the present study, as well as the previous investigation in 2015 [ 19 ], showed that job satisfaction among the graduates was higher. Furthermore, a majority of graduates answered maybe or definitely yes to the question of whether they would start the same career if they were to choose again, thus indicating that most of the graduates were satisfied with their choice of career.…”
Section: Discussioncontrasting
confidence: 82%
“…6 Relationship with patients is an important factor of job satisfaction for Chinese physicians. 7 Meanwhile, the increasing risk of medical litigation can lead to physicians recommending 'safer' procedures to avoid litigation, which may increase medical cost, reduce access to care, and even bring physical harm to patients. 8,9 Medical expenditures are positively related to the incidence of malpractice lawsuits.…”
Section: Introductionmentioning
confidence: 99%
“…Stresses brought by medical disputes have resulted in physical and psychological problems to physicians, indicated by lower sleep quality and self‐reported health 6 . Relationship with patients is an important factor of job satisfaction for Chinese physicians 7 . Meanwhile, the increasing risk of medical litigation can lead to physicians recommending ‘safer’ procedures to avoid litigation, which may increase medical cost, reduce access to care, and even bring physical harm to patients 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…20 In addition to the barriers to error disclosure that also exist in other countries (e.g., the fear of litigation, and the lack of a disclosure culture, skill, and/or guidance), 2,11,25,26 Chinese health care providers are extremely fearful of patient violence in response to disclosure, as it is a frequent phenomenon. 27 However, failure to disclose errors is unacceptable, and they should be revealed with transparency and integrity. Error disclosure is an important issue because it is a promising way to reduce the number of lawsuits against a health care institution, enhance patient satisfaction, and provide relief for the health care providers who were involved in the incidents.…”
mentioning
confidence: 99%